Recuperação da informação: estudo da usabilidade na base de dados Public Medical (PUBMED) - Coelho, Odete Máyra Mesquita (2013)
This study, part of the Master research, presented to the Graduate Program in Information Science from the Federal University of Paraíba, which proposes to investigate the understanding that residents have about the process of information retrieval in the database Public Medical , better known as PubMed, taking into account aspects of usability in humancomputer interaction, the resources available and the level of user satisfaction with the search process. Researches on Information Retrieval in specialized databases is current and very relevant, since the development of electronic technologies and digital information and communication has increased the storage capacity in databases, and has facilitated access and users autonomy. The methodological approach includes the in the first phase of this study an heuristic evaluation of the interface of the base referenced, based on the guidelines proposed by Nielsen and Tahir (2002). In the second stage, it intends to implement the tests with users through interviews and questionnaires.